A history evaluation modelling and forecastation of water quality in shallow lake. (1st November 2012) - Xu, Ligang; Pan, Jizheng; Jiang, Jiahu; Zhao, Hongbo; Liu, Caihong
Abstract: The frequent outbreaks of water eutrophication in Gehu Lake are regarded as one of the most troublesome environmental issues in Southeast China. Based on the water's potential capacity to accept pollutant loads, a catchment‐scale environmental management system was established to ensure inflows of clean water into Taihu Lake. Considering the complexity of the hydrological regimes operating within the river‐network plain, the capacities of the water environment for loads of COD and nutrients were estimated using the Water Quality Analysis Simulation Program, Version 7.3 (WASP 7.3) model. The calibration and the verification of this model were based on water quality measurements during the period 2009–2010. The variables of water quality that were examined are COD, NH4 ‐N, TN and TP. The simulated distributions of the COD, NH4 ‐N, TN and TP in the water column agree with the observations, but it indicates that more measurements are needed to verify the predictability of the simulations. The simulation results show that the average relative error is small, and the change trend of each indicator is consistent. The results have shown that the WASP model can be used to evaluate the future water quality changes in case that the pollution continues with the same rate. The work presented in this paper is expected to be a theoretical basis in exploring the degradation mechanism for self‐purification capacity of water bodies and in designing and constructing of Gehu Lake ecosystem restoration goals.